Association between pediatric asthma care quality and morbidity and English language proficiency in Ohio - Montgomery, Martha P. (J Asthma, 2018)
OBJECTIVE: Limited English proficiency can be a barrier to asthma care and is associated with poor outcomes. This study examines whether pediatric patients in Ohio with limited English proficiency experience lower asthma care quality or higher morbidity. METHODS: We used electronic health records for asthma patients aged 2–17 years from a regional, urban, children’s hospital in Ohio during 2011–2015. Community-level demographics were included from U.S. Census data. By using chi-square and t-tests, patients with limited English proficiency and bilingual English-speaking patients were compared with English-only patients. Five asthma outcomes—two quality and three morbidity measures—were modeled using generalized estimating equations. RESULTS: The study included 15352 (84%) English-only patients, 1744 (10%) patients with limited English proficiency, and 1147 (6%) bilingual patients. Pulmonary function testing (quality measure) and multiple exacerbation visits (morbidity measure) did not differ by language group. Compared with English-only patients, bilingual patients had higher odds of ever having an exacerbation visit (morbidity measure) (adjusted odds ratio [aOR], 1.4; 95% confidence interval [CI], 1.2–1.6) but lower odds of admission to intensive care (morbidity measure) (aOR, 0.3; 95% CI, 0.2–0.7), while patients with limited English proficiency did not differ on either factor. Recommended follow-up after exacerbation (quality measure) was higher for limited English proficiency (aOR, 1.8; 95% CI, 1.4–2.3) and bilingual (aOR, 1.6; 95% CI, 1.3–2.1), compared with English-only patients. CONCLUSIONS: In this urban, pediatric population with reliable interpreter services, limited English proficiency was not associated with worse asthma care quality or morbidity.